Fostering Inclusivity: Exploring the Impact of Identity Safety Cues and Instructor Gender on Students' Impressions and Belonging. (April 2023) - Maimon, Melanie R.; Howansky, Kristina; Sanchez, Diana T.
Background: Students with marginalized identities can experience identity threats in higher education. Instructors can help improve student outcomes by using identity safety cues (ISCs), which signal to marginalized groups that their identities are valued. Objective: The purpose of this study was to examine whether including ISCs in course syllabi could improve students' belonging-related outcomes and whether these outcomes differ based on instructor gender. Method: Using an experimental design, undergraduate students viewed a syllabus that included or excluded ISCs from either a White male or female professor. Participants reported their anticipated belonging and instructor impressions. Results: Participants reported greater expected engagement and field belonging and had more positive impressions of the instructor when the syllabus included ISCs compared to the control syllabus. Instructor gender had a minimal impact on participants' outcomes and impressions. Conclusion: This work demonstrates including ISCs in course syllabi can positively impact students when course instructors are White men or women. Teaching Implications: ISCs improved participants' anticipated engagement and field belonging regardless of instructor gender. This work suggests instructors can improve students' first impressions and intentions by including ISCs in their course syllabi.